Farmer groups as ICT Hubs: Findings from a cluster-randomized controlled trial in Malawi - Ragasa, Catherine; Ma, Ning; Hami, Emmanuel (International Food Policy Research Institute, 2024)
Many rural producer groups face poor management practices, low productivity, and weak market linkages. An information and communication technology (ICT)-based intervention bundle was provided to producer groups to transform them into ICT hubs, where members learn about and adopt improved management practices and increase their productivity and incomes. The intervention bundle includes phone messages and videos, promotion of the call center/hotline, and facilitation of radio listening clubs and collective marketing. The study, a cluster-randomized controlled trial, randomly assigned 59 groups into treatment groups and 59 into control groups. After 18 months of interventions, results show positive but small impact on crop sales (USD65 per household) and no impact on productivity. The income effect was mainly from Kasungu and Nkhota-kota, which experienced increased production and sales of rice, soybean, and groundnut and received higher prices due to collective marketing. Farmers in Kasungu and Nkhota-kota improved a few agricultural management practices, while farmers in other districts did not improve their management practices. Results show more farmers accessing phone messaging on agriculture and markets, greater awareness and use of the call center, more listening groups established, and more farmers—especially women—joining these groups. Nevertheless, coverage and uptake remain very low, which are likely reasons for the limited impact.